2019
DOI: 10.1371/journal.pone.0217304
|View full text |Cite
|
Sign up to set email alerts
|

Physical events occurring during the cryopreservation of immortalized human T cells

Abstract: Cryopreservation is key for delivery of cellular therapies, however the key physical and biological events during cryopreservation are poorly understood. This study explored the entire cooling range, from membrane phase transitions above 0°C to the extracellular glass transition at -123°C, including an endothermic event occurring at -47°C that we attributed to the glass transition of the intracellular compartment. An immortalised, human suspension cell line (Jurkat) was studied, using the cryoprotectant dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 30 publications
(46 reference statements)
3
53
0
Order By: Relevance
“…The data presented in Fig 3 indicates that extending frozen storage from 3 months to 17 years has no significant effect on the post-thaw outcome of the samples. To ensure the safe, long-term storage of apheresis samples it is critical that the samples are held, continuously, below the glass transition temperature of the cryoprotectant solution, some -120°C for DMSO-based solutions [ 6 , 32 ]. Studies with other biological systems have shown this to be effective, and necessary, for decades [ 4 , 33 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data presented in Fig 3 indicates that extending frozen storage from 3 months to 17 years has no significant effect on the post-thaw outcome of the samples. To ensure the safe, long-term storage of apheresis samples it is critical that the samples are held, continuously, below the glass transition temperature of the cryoprotectant solution, some -120°C for DMSO-based solutions [ 6 , 32 ]. Studies with other biological systems have shown this to be effective, and necessary, for decades [ 4 , 33 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect is used in vitrification processes for cryo-conservation without damaging ice crystals 40 . For our studies Tg can only be estimated, but Meneghel et al demonstrated a Tg around − 47 °C for human T-cells in suspension 41 . Although our cells were not in suspension and no T-cells, cytoplasm might be of similar composition.…”
Section: Discussionmentioning
confidence: 77%
“…Cooling rates were varied from 0.5 to 2 • C/min using a VIA Freeze TM Duo controlled-rate freezer starting from 4 • C and stopping at −80 • C before transferring vials to vapor phase liquid nitrogen storage (Figure 2). The vapor phase of liquid nitrogen (below −170 • C) was chosen since this is below the glass transition temperature of cells in cryoprotectant (∼−120 • C), and biological material is known to be highly stable at this temperature with no changes in cell viability for over 1 year (Silani et al, 1988;Massie et al, 2013;Meneghel et al, 2019). The recovery of mDA neural progenitor cells was performed by either thawing vials slowly in air at 4 • C or rapidly in a water-bath set to 37 • C. Cell viability was assessed by Trypan blue exclusion immediately upon thawing prior to plating in mDA neuronal differentiation conditions, and again at 24 h post-thawing.…”
Section: Resultsmentioning
confidence: 99%